НЛО
Мыслитель
(9200)
14 лет назад
Pb(NO3)2+H2S = PbS+ 2HNO3
Pb(2+) + 2NO3- + 2H+ + S(2-) = PbS + 2H+ + 2NO3-
Pb(2+) + S(2-) = PbS
2AgNO3 + FeCl2 = 2AgCl + Fe(NO3)2
2Ag+ + NO3- + Fe(2+) + 2Cl- = 2AgCl + Fe(2+) + 2NO3-
2Ag+ + 2Cl- = 2AgCl
Штирлиц
Высший разум
(318216)
14 лет назад
Pb(NO3)2+H2S = PbS(осадок) + 2HNO3
Pb(2+) + 2NO3- + 2H+ + S(2-) = PbS(осадок) + 2H+ + 2NO3-
Pb(2+) + S(2-) = PbS(осадок)
2AgNO3 + FeCl2 = 2AgCl + Fe(NO3)2
2Ag+ + NO3- + Fe(2+) + 2Cl- = 2AgCl(осадок) + Fe(2+) + 2NO3-
2Ag+ + 2Cl- = 2AgCl(осадок)
Светлана Козлова
Знаток
(387)
14 лет назад
1)H2S + Pb(NO3)2 -> PbS (в осадок) + 2HNO3
2Н + S + Pb +2NO3 - PbS + 2H + 2NO3
S+Pb-PbS
2) 2AgNO3+FeCl2 --> 2 AgCl (в осадок) + Fe(NO3)2
2Ag +2NO3+Fe+2Cl-2AgCl+Fe+2NO3
Ag+Cl-AgCl
еще степени поставить надо везде